OS ASPECTOS PROMOCIONAIS DO ESPAÇO CÚLTICO: UM ESTUDO DE CASO DO TEMPLO DE SALOMÃO - CONCEIÇÃO, JONATHAN GORDIM (2019)
The purpose of this work is to study and analyze the promotional campaigns used in the cultic space and its object of study is the New Temple of Solomon (NTS), which was conceived and built by the Universal Church of the Kingdom of God. Several characteristics that relate to or concern the NTS were raised; such as its location, construction, decoration, competing churches, use of sensorial marketing and the experiences and marketing techniques employed in the services and its construction will be seen in this case study. In addition to being the world headquarters of the IURD, the NTS is the largest denomination temple, and it is in its unique architecture that the great brand differentiation and strength of the IURD is demonstrated. The NTS emerges as a brand repositioning of the IURD and altering even its liturgy and worship that transcends its walls and influences by making the liturgy and worship of its faithful distributed in all the churches of the network appropriate in the new standard of the IURD, in Brazil or in the world. Looking at this object of study, we noticed the use of elements that used to be used mainly in large retail chains were implemented strategically in the NTS transforming this mega church into a Concept Store.